Risiko Periode Pranatal Dan Implikasi Perkembangan Pranatal Dalam Layanan Konseling - Aulia Indira (Pusat Riset dan Inovasi Nasional, 2024)
The baby's development and the mother's condition can also be affected by the problems that arise. This article will discuss prenatal development and birth for children because we have little understanding of how this period influences human development, of the issues associated with it, and of the factors and effects experienced by prospective parents. The purpose of this discussion is to find out the risks (dangers) of the prenatal period, to find out the implications of prenatal development in counseling services